Innovative technologies and non-invasive procedures in bariatric surgery - Dargent, Jerome (Springer Paris, 2013)
The majority of the obese population still does not take advantage of the available surgical possibilities. Clinical research should be oriented towards less invasive procedures that could be accepted by the mainstream. In 2012, most non-invasive bariatric techniques are still not standardized or sufficiently assessed, but they are being constantly upgraded. The purpose of this book is to spark a discussion between experts from around the world, and to gather relevant information on new technologies that will make it possible to enlarge the vision of bariatric care to a growing number of morbid obese and non-morbid obese patients.